2012
DOI: 10.3389/fnsys.2012.00002
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus does not require macroscopic tonotopic map reorganization

Abstract: The pathophysiology underlying tinnitus, a hearing disorder characterized by the chronic perception of phantom sound, has been related to aberrant plastic reorganization of the central auditory system. More specifically, tinnitus is thought to involve changes in the tonotopic representation of sound. In the present study we used high-resolution functional magnetic resonance imaging to determine tonotopic maps in the auditory cortex of 20 patients with tinnitus but otherwise near-normal hearing, and compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
98
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 70 publications
7
98
0
Order By: Relevance
“…2007) and the transient N1 response known to localize to distributed sources in the region of the auditory parabelt (called here nonprimary auditory cortex, A2). ASSR sources show a coarse but consistent low-frequency anterolateral, high-frequency posteromedial tonotopic organization (Pantev et al, 1996;Wienbruch et al, 2006;Gander et al, 2010a) that reflects the summation of extracellular field potentials across two cochleotopic maps with strong low-frequency anterolateral and high-frequency posteromedial activations in Heschl's gyrus (Langers et al, 2012). In contrast, N1 sources localize to distributed and cytoarchitectonically heterogeneous regions of A2 (Godey et al, 2001) where tonotopy is lacking or not strongly expressed (Schreiner and Cynader, 1984;Langers et al, 2007;Lütkenh€ oner et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…2007) and the transient N1 response known to localize to distributed sources in the region of the auditory parabelt (called here nonprimary auditory cortex, A2). ASSR sources show a coarse but consistent low-frequency anterolateral, high-frequency posteromedial tonotopic organization (Pantev et al, 1996;Wienbruch et al, 2006;Gander et al, 2010a) that reflects the summation of extracellular field potentials across two cochleotopic maps with strong low-frequency anterolateral and high-frequency posteromedial activations in Heschl's gyrus (Langers et al, 2012). In contrast, N1 sources localize to distributed and cytoarchitectonically heterogeneous regions of A2 (Godey et al, 2001) where tonotopy is lacking or not strongly expressed (Schreiner and Cynader, 1984;Langers et al, 2007;Lütkenh€ oner et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
“…None of them had a history of neurological or psychiatric disorders. Subjects' characteristics are listed in Table 1 (Langers et al 2012). Except for the presence of tinnitus in the patient group, all subjects were selected to have normal or near-normal hearing up to 8 kHz.…”
Section: Participantsmentioning
confidence: 99%
“…However, tonotopic reorganizations and altered efferent activity may not be present in all cases of tinnitus. Functional MRIs performed by Langers, de Kleine and van Dijk (2012) indicated that macroscopic tonotopic reorganization is not common for tinnitus patients with normal hearing thresholds 19 . Furthermore, IC neural recordings performed by Bauer et al (2008) revealed significantly increased contralateral IC spontaneous spiking and cross fiber synchrony in chinchillas with tinnitus (as indicated by behavioral paradigms) with no evidence of a tonotopic edge effect or tuning frequency shift 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of tinnitus accompanied by hearing loss, it is believed that tinnitus pitch is either localized in the "edge" frequencies or within the lowest regions of the hearing loss 19 . If tinnitus pitch exists within the lowest portions of the corresponding hearing loss, then theoretically, specific subcortical neural fibers act as the direct factor of tinnitus percept 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation